VALUE-BASED INQUIRY LEARNING APPROACH IN SHAPING THE MORALITY OF THE DIGITAL NATIVE GENERATION - Rohima, Ulpaini Roudhotur; Yolanda, Dinda; Hidayat, Muslih; Koiruman, Joko Andi (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The Digital Native generation, having grown up immersed in technology, faces unique challenges in moral development, particularly in relation to Islamic values. With the rise of digital content influencing their perceptions of morality, it is crucial to explore effective educational strategies that integrate traditional values with modern learning methods. One such approach is value-based inquiry learning, which promotes active engagement and moral exploration. Purpose: This study aims to examine the implementation of a value-based inquiry learning strategy to enhance students' understanding and practice of Islamic moral values, particularly among the Digital Native generation at MTs Darul Ishlah, Lubuklinggau. The inquiry-based learning method, which involves group discussions, value exploration, and role-playing, is considered effective in helping students internalize Islamic values in their daily lives. Method: This research uses a qualitative approach with observation, interviews, and documentation techniques to assess the impact of this strategy on character development. Result: The findings show that value-based inquiry learning significantly improved students' understanding of Islamic moral values, such as honesty, responsibility, and mutual respect, and motivated them to apply these values in real-life situations. The support of visual media and technology further enhanced students' engagement and helped make the learning material more relevant to their digitally-based lives. Challenges included time limitations that hindered deeper exploration and reflection, as well as students’ initial difficulties in adapting to participatory learning methods. This study recommends adjusting time allocations and applying more flexible methods to ensure the optimal implementation of this strategy. ConclusionOverall, value-based inquiry learning has proven to be an effective approach for shaping students' Islamic character and is well-suited to the needs of the Digital Native generation in the digital age.